Envisioning the Veracity of Digital Ecosystem in Improvising Effective Pandemic Response - Bharti, Aditya; Krishnan, Supriya; Bharti, Sudhanshu Kumar (Frontiers in Blockchain, 2021)
The obfuscation and the kind of cover-up or delay in COVID-19 crisis-response put the veracity of global healthcare settings at stake and appended a biological dimension to geopolitical tensions. The ineffectual surveillance systems of public health and social measures cause the swift viral transmission pace amid mounting death toll and necessitate for an effective, cohesive and strategic response. The digital ecosystem can serve the purposes intended in a transparent and immutable manner. This article highlights the problems encountered by the global healthcare settings in responding to pandemic and throws light on how the global digital ecosystem can handle crisis by managing the landscape radically through transparent information sharing via internet of things (IoT) with the data being utilized by artificial intelligence (AI) and Blockchain technologies on a cross-disciplinary collaborative basis. It will help to develop and provide borderless solutions of public health via monitoring, surveillance, detection and prevention as well as digi-tools assisted repurposed treatment by the use of authentic and decentralized distributed database that makes all contributors (participating countries, United Nations Organisations, the world medical associations and global media and publications) accountable, inviolable and efficient to tackle healthcare processes. It will extricate a blanket ban on information sharing thereby bringing democracy and freedom.